Potent, Selective, and CNS-Penetrant Tetrasubstituted Cyclopropane Class IIa Histone Deacetylase (HDAC) Inhibitors - Luckhurst, Christopher A. (ACS Med Chem Lett, 2015)
[Image: see text] Potent and selective class IIa HDAC tetrasubstituted cyclopropane hydroxamic acid inhibitors were identified with high oral bioavailability that exhibited good brain and muscle exposure. Compound 14 displayed suitable properties for assessment of the impact of class IIa HDAC catalytic site inhibition in preclinical disease models.